Value addition and evaluation of nutritional quality in taro (colocasia esculenta (L.) schott) - Shamsudeen Liya (Department of Processing Technology, College of Agriculture, 2002)
A study on "Value addition and evaluation of nutritional quality in taro (Colocasia esculenta (L.) Schott)" was carried out in the Department of Processing technology, College of Agriculture, Vellayani, Thiruvananthapuram during the period 1999- 2001. The objectives of the study were to evaluate four cultivars of colocasia for nutritional quality, to examine the potentiality of developing value added products using colocasia and to assess the storage and shelf life of the colocasia products. The nutritional quality of four cultivars ie., Pathanamthitta local, Vellayani local, Thamarakannan and Sree Rashmi were evaluated. Corms of Pathanamthitta local had the highest starch and calcium oxalate content. Vellayani local exhibited the highest protein and vitamin C content while Thamarakannan had the highest total sugar content. The crude fibre contents of all the four cultivars were on par. Sree Rashmi recorded the maximum organoleptic quality. In case of leaves protein content and organoleptic quality were high in Sree Rashmi while total sugars was maximum in